A Decade of Progress on Scaling up Health and Nutrition Interventions in India: a Countdown to 2030 Case Study (P04-115-19). (13th June 2019) - Menon, Purnima; Nguyen, Phuong; Avula, Rasmi; Mani, Sneha; Tran, Lan; Victora, Cesar
Abstract: Objectives: India rolled out ambitious program efforts for health and nutrition (H&N) in 2005–06, scaling up community H&N services through the National Rural Health Mission and the Integrated Child Development Services (ICDS). Evidence on the combined reach and impact of these programs on closing equity gaps is limited. We aimed to assess how coverage and equity in interventions have changed between 2006 and 2016. Methods: We used two rounds of National Family Health Survey data collected in 2006 and 2016 ( n  = 36, 850 and 190, 898 mother-child dyads with the last child aged of 0–5 y, respectively). We selected a key set of interventions in India's policy frameworks, spanning the continuum of care for maternal, newborn and child H&N. We examine progress over time at national and state level, then assess equity and changes in equity by state, urban/rural, caste and socioeconomic status using concentration and slope indices. We complemented the data analysis with policy analyses and highlight state-specific success case studies. Results: Coverage of all H&N interventions improved, and equity gaps decreased at all levels examined between 2006 and 2016. Institutional deliveries, some components of antenatal care and immunization reached high coverage (80–90%). For nutrition, consumption of iron folic supplements during pregnancy nearly doubled (from 16 to 30%) and receiving food supplements during lactation tripled (from 15 to 48%). Although the trends are positive, achieving full coverage of interventions to every woman and every child remains a significant challenge. Levels of achieved coverage and trends over time vary tremendously by state, highlighting governance and implementation successes and challenges. Health interventions reach more rich than poor, whereas ICDS interventions are overwhelmingly used by the poor. Equity gains for antenatal care, institutional delivery and immunizations for the poor come primarily from increased use of public sector services. Conclusions: India's progress in coverage of H&N interventions and narrowing of equity gaps in the last decade are significant achievements. As India looks ahead to the Sustainable Development Goals, a stronger focus on closing gaps in coverage, state-by-state, is needed. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by IFPRI.